Monitoring Dynamics, Structure, and Magnetism of Switchable Metal–Organic Frameworks via 1H‐Detected MAS NMR. Issue 40 (2nd September 2021) - Blahut, Jan; Lejeune, Arthur L.; Ehrling, Sebastian; Senkovska, Irena; Kaskel, Stefan; Wisser, Florian M.; Pintacuda, Guido
Abstract: We present a toolbox for the rapid characterisation of powdered samples of paramagnetic metal–organic frameworks at natural abundance by 1 H‐detected solid‐state NMR. Very fast MAS rates at room and cryogenic temperatures and a set of tailored radiofrequency irradiation schemes help overcome the sensitivity and resolution limits often associated with the characterisation of MOF materials. We demonstrate the approach on DUT‐8(Ni), a framework containing Ni 2+ paddle‐wheel units which can exist in two markedly different architectures. Resolved 1 H and 13 C resonances of organic linkers are detected and assigned in few hours with only 1–2 mg of sample at natural isotopic abundance, and used to rapidly extract information on structure and local internal dynamics of the assemblies, as well as to elucidate the metal electronic properties over an extended temperature range. The experiments disclose new possibilities for describing local and global structural changes and correlating them to electronic and magnetic properties of the assemblies. Abstract : Paramagnetic DUT‐8(Ni) metal–organic frameworks were characterised over an extended temperature range with 1 H‐detected NMR techniques under fast magic‐angle spinning. The sensitivity of the approach allows rapid access to structure and dynamics of the organic linkers as well as the electronic properties of the metal centres in these materials.